Challenges in Implementing Minimum Wage in Indonesian Footwear Industry: Tantangan Penerapan Upah Minimum di Industri Alas Kaki Indonesia - Anthonyus Hudan Perdana Anthonyus Hudan; Sri Budi Purwaningsih (Academia Open, 2022)
The article discusses the implementation of minimum wage for workers in a footwear company based on the Indonesian Law No. 11 of 2020 on Job Creation. The study used the juridical-empirical research method to analyze the wage system and assess the implementation of minimum wage. The results indicate that the current wage system is not effective and requires improvement. The study aims to provide a basis for further research that examines similar issues related to labor and wage systems in Indonesia. The article highlights the fundamental right of every citizen to obtain employment and a living wage, and the challenges that hinder the implementation of this right. Highlights: Study on minimum wage implementation in Indonesian footwear company finds system ineffective. Fundamental right to living wage hindered by challenges in Indonesia. Research highlights need for improvement in labor and wage systems in Indonesia. Keywords: minimum wage, footwear company, Indonesian Law No. 11 of 2020, wage system, labor rights